Pengaruh Motivasi Kerja Terhadap Disiplin Kerja Karyawan Di Rocky Plaza Hotel Padang - Putri Defri Yanti; Hijriantomi Suyuthie (JURNAL PENDIDIKAN DAN KELUARGA, 2020)
This study aims to determine the effect of work motivation on employee work discipline at Rocky Plaza Hotel Padang..1.This type of research is descriptive quantitative research with causal methods. The population in this study were all employees at Rocky Plaza Hotel Padang. The research sample amounted to 54 employees using.1.the sampling technique is the proportionate stratified random sampling technique..1.Data collection techniques are carried out by using a questionnaire (questionnaire) with a Likert scale that has been tested for validity and reliability. Data were analyzed by simple linear regression testing through.1.the help of the SPSS Computer Program version 16.00. the results of the study show: 1) Work Motivation employees at Rocky Plaza Hotel Padang are in the good category (74.07%). 2) Employee Discipline is in a very good category (59.26%). 3) R Square 0.155 and a significance value of 0.03 which means that.1.there is a significant effect between work motivation on work discipline of 15.5% while the remaining 84.5% is influenced by other factors.